THE PROCESS OF KHON PERFORMANCE PRODUCTION IN SECONDARY-LEVEL DEMONSTRATION SCHOOLS IN BANGKOK - Puangbupha, Phanida; Boonpeng, Suphannee (Fine Arts Journal: Srinakharinwirot University, 2026)
Background and Objectives: This research article is part of the thesis “Khon Performance in Demonstration Schools.” The study aims to examine the process of Khon performances production in secondary-level demonstration schools in Bangkok, with particular attention to instructional practices and the conceptual frameworks used to transmit knowledge for organizing Khon performances. Methods: This study employs a qualitative research design, including documentary research (books, research studies, and relevant scholarly articles). Additionally, observations were conducted in two methods; 1) participant observation, in which the researcher assisted teaching Khon and Thai classical dance, worked as a stage director, and participated in publicizing the performances, and 2) non-participant observation, by watching live Khon performances and reviewing video recordings of various demonstration school performances. The scope of the research includes the conceptual frameworks, teaching and learning methods, and the process of organizing Khon performances in demonstration schools. Key Findings: Preliminary findings indicated that three secondary-level demonstration schools in Bangkok have consistently organized Khon performances for at least five consecutive years. Each of these schools applies different teaching approaches based on their respective educational philosophies: 1) Srinakharinwirot University Prasarnmit Demonstration School (Secondary) applies the Theory of Multiple Intelligences in its curriculum, emphasizing hands-on practice to develop both physical and mental proficiency. Khon is offered as both compulsory and elective courses for students in grades 7-12. Performers are selected through an audition process, and performances are held annually and on special occasions. 2) Kasetsart University Laboratory School, Center for Educational Research and Development adopts the “1 Morality, 5 Disciplines” (1 ศ 5 ส) approach, which integrates Thai cultural traditions into education. Khon is taught through an extracurricular club at the secondary level, combining theoretical learning with practical training. Students practice Khon alongside storytelling activities, and performances are staged on various occasions. 3) Darunsikkhalai School applies the Constructionism Learning Theory, integrating Khon into a required course structured as a project-based learning subject in Grade 7. Students develop theoretical understanding through research and report writing, while practical training is provided by external instructors. Casting and training are determined in part by students’ physical attributes, and performances are organized for special events. Implications of the Study: Demonstration schools that organize Khon performances adopt different teaching and learning approaches based on their educational philosophies. All schools place significant emphasis on practical training to ensure that students develop technical skills and a profound understanding of Khon as a traditional performing art. Khon performances production in demonstration schools play a vital role in preserving and promoting Thai cultural heritage among young people. Conclusion and Future Research: The findings indicate that Khon performances production in demonstration schools not only contributes to the preservation of Thailand’s cultural heritage but also plays an essential role in enhancing students' learning skills and personal development through the rehearsal and performance processes. Future studies should explore other concepts or theories that can be applied to Khon education.